Transit Across the Alps: the Problem and Approaches Towards a Solution - Wilfried Puwein (Austrian Institute of Economic Research (WIFO), 2006)
The transport of road goods across the Alps constitutes a problem both for European transportation and for the Alpine environment. Austria and Switzerland have made a number of attempts to decelerate the growth in lorry transit volume and shift transport onto the rail modes. After ten years, such efforts can be deemed to have failed. The envisaged new rail lines across the Alps should procure higher transport capacities and shorter transport times for the railways, but will hold their own against the road only when the transport flow is improved and prices are kept down. Accordingly, it will be virtually impossible for the railways to pay the full cost of transalpine transit links. In Switzerland, much of the financing burden of the rail infrastructure investments is shifted onto road transport. In Austria, the cross-financing permitted under the "Eurovignette" Directive will cover only a small fraction of the actual investment costs of the planned new Brenner tunnel. An ecologically sustainable and economically efficient solution proposed is to set up a quota scheme for Alps-crossing lorries in the form of emission certificates which are to be auctioned and traded.
Keywords: 330; road transport; transalpine; transit quota scheme; alps-crossing; emission; certificates; Transitverkehr; Straßenverkehr; Verkehrsinfrastruktur; Wirkungsanalyse; Alpenraum; Österreich; Schweiz